The relationship between active hand and ear advantage in the native and foreign language - Mildner, Vesna (Array, 2005)
In an experimental design involving two auditorily presented competing commands (one to each ear), 144 right-handed subjects (72 male and 72 female) were asked to provide motor responses. Half of each group of subjects was responding with their right hand and the other half with the left. The test was applied in the subjects' native language (Croatian) and in English, which they had learned as a foreign language. Ear advantage was determined by calculating laterality indices from the order of responding to the commands. On average, right-ear advantage was found in all conditions. Analysis of results revealed the effect of the active hand in Croatian (with significant decrease in the right-ear advantage when using the left hand). The same trend failed to reach significance in English. In responses to English stimuli, there was a significant effect of gender (with men exhibiting a lower right-ear advantage than women). The same trend was not significant for Croatian stimuli. The consistently lower right-ear advantage found in male subjects is contrary to the traditional assumptions that men are more lateralized than women and warrants further investigation.